Influence of beverage temperature on exercise performance in the heat: A systematic review - Burdon, C. A.; O'Connor, H. T.; Gifford, J. A.; Shirreffs, S. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Purpose: Increased core temperature (Tc), impaired cardiovascular function, and dehydration contribute to fatigue during prolonged exercise in the heat. Although many studies have examined mechanisms addressing these factors, few have investigated the effect of cold beverage temperature on thermoregulation and exercise performance in the heat. Methods: Citations from MEDLINE (Ovid), Sport Discus (EBSCOhost), AUSPORT and AusportMed (Informit), Web of Science, and SCOPUS were identified from the earliest record until September 2008 using the search terms drink temperature, beverage temperature, fluid temperature, water temperature, and cold fluid combined with body temperature and thermoregulation. To be included, studies needed to assess core or rectal temperature during exercise in moderate or hot environmental conditions. After quality rating was completed by 2 reviewers, the difference in mean Tc and exercise performance was calculated. Results: Ten studies meeting search inclusion criteria were available for analysis. Three were excluded because sufficient detail or statistical data were not reported. A meta-analysis was not performed because the studies were deemed too different to group. Three of the remaining 7 studies found modulated Tc with cold beverage consumption, and from the 4 that conducted exercise performance tests, performance improved by 10% with cold fluids. Conclusion: Cold fluid may attenuate Tc rise and improve exercise performance in the heat; however, study findings are mixed. Research using well-trained athletes and fluid-ingestion protocols replicating competition scenarios is required. Potential sensory effects of cold fluid in maintaining motivation also need to be assessed as a mechanism underpinning improved performance.